Analisis Validasi Produk Dengan Menggunakan Value Proposition Canvas Pada Startup Nominus - Taufiqurrohman, Muhammad Rizal; Hasbi, Imanuddin (eProceedings of Management, 2024)
NoMinus is a StartUp that provides a platform in the form of an Instagramshop where users can sell and buy new andpre-loved clothes. NoMinus offers a variety of products, including men's, women's, and children's clothing. ProductValidation Analysis needs to be carried out by NoMinus to minimize the risk of failure and find out which areas needimprovement and adjustment. Product validation analysis in this research uses the Value Proposition Canvas. Datacollection in this study used questionnaire, interview and observation methods. Respondents in this study totaled 100people. The results showed that customers were satisfied with the products and services offered by NoMinus. but thereare several areas that need more attention. therefore the Value Proposition Canvas can be used to create aninnovation to help NoMinus minimize the risk of failure.Keywords-NoMinus, pre-loved, value proposition canvas and product validation analysis